Upaya Peningkatan Sarana dan Prasarana untuk Mendukung Kualitas Pembelajaran di SDN 01 Jatibarat-Pecangaan - Eka Nor Shoviana; Ro’ifatuzzahroh Ro’ifatuzzahroh; Siti Sallyesiah Muntrika Sari; Fina Salmah Putri; Zidniy Bima Tasya; Nur Rohman (Jurnal Pendidikan Dirgantara, 2025)
This study aims to examine the challenges and formulate strategies for improving educational facilities and infrastructure in order to enhance the quality of learning at SDN 01 Jatibarat. Good learning quality is highly dependent on the availability of adequate educational infrastructure, so it is important to identify existing obstacles and design appropriate solutions. This study used a qualitative descriptive approach with data collection techniques through direct observation, in-depth interviews with teachers and the principal, documentation, and distribution of questionnaires to the school community and committee. The results of the study indicate that the school faces various limitations, particularly in terms of the availability of adequate classrooms, limited interactive learning media, and lack of access to educational technology such as computers and internet networks. These challenges impact the teaching and learning process less than optimal. To address this, the school has taken several strategic steps, including conducting regular needs assessments, collaborating with the school committee and the surrounding community, and submitting assistance proposals to the local government and relevant agencies. These improvement efforts are carried out collaboratively and in a targeted manner, involving all stakeholders so that infrastructure improvements can support the creation of a safe, comfortable, and stimulating learning environment. This study concludes that an active and synergistic role between schools, parents, the community, and the government is crucial in supporting the achievement of quality basic education. The involvement of all parties is key to achieving the sustainability of educational facilities and infrastructure improvement programs.